Analisis Pengendalian Mutu pada Penanganan Udang Vaname Beku Metode IQF (Individually Quick Freezing) - Putriana Putriana; Yusri Muhammad Yusuf; Andi Baso Adil Natsir (Asosiasi Riset Ilmu Tanaman dan Hewan Indonesia, 2025)
The study aims to evaluate the flow of material in the handling process and the quality control measures implemented throughout the production stages. The research employs a qualitative descriptive method, utilizing primary data collected through direct observation, interviews, and secondary data from relevant literature. The findings indicate that the IQF method significantly preserves the quality and freshness of the shrimp, ensuring compliance with international export standards. The study also identifies strengths, weaknesses, opportunities, and threats (SWOT analysis) related to the company's operations, highlighting the importance of maintaining high-quality raw materials and efficient production processes. Recommendations for improving quality control practices and enhancing operational efficiency are provided, emphasizing the need for continuous training and investment in modern technology.